Au fil de nos souvenirs : le 17 octobre 1961, emblème des violences policières - Clotilde Lebas (Revue des Mondes Musulmans et de la Méditerranée)
Through the analysis of an event eclipsed and forced back by French collective history – the gathering of October 17th, 1961 of Algerians demonstrating against curfew and its bloody repression – this article intends to think about the way our memories express themselves and how personal experiments can be given a shared sense. It shows how a traumatic event can constitute a memorial landmark which generates substitutions and successive transformations. Then, the reference to a unique event becomes less visible and scatters in various directions. From an evocation to another, from an entrepreneur de mémoire to another, the memory of October 17th, 1961, supported by photographs left by Kagan, becomes the symbol of police violence. This example illustrates the complexity of memory dynamics by revealing how an event can come back, by the detour of photography, as a fact or a trace, and be reinvested in a present time where it still makes sense.